Synthesis and development of C3 symmetric tridentate olefin ligands - Nyberg,Vilhelm (2025)
Chiral C3-symmetric molecules are an important class of compounds with applications in asymmetric catalysis and drug discovery. Few synthetic methods exist to synthesize this class of molecules in a step-economic and concise manner. This work explores a range of chemical transformations to functionalize the D3-symmetric (a,e,i)tribenzo(5,6,11,12,17,18) hexadehydro[12]annulene into C3-symmetric planar chiral derivatives, which are both conceptually interesting, and of value as potential ligands in asymmetric catalysis on account of their inherent chirality. Herein, we present our efforts of breaking the symmetry of this peculiar system, including new methodology to access (a,e,i)tribenzo[12]annulene in high yield via hydrosilylation and subsequent alcoholysis and protodesilylation. We also present the preparation of an enantiopure cross-coupling partner, which holds the potential to enable a great variety of compounds in this elusive class of C3-symmetric chiral olefins.
Keywords: organic chemistry; C3 symmetry; hydrosilylation; protodesilylation; symmetric addition; symmetric substitution